Pengaruh Motivasi Kerja Terhadap Pengembangan Karir Dosen di Lingkungan Fakultas Kesehatan Masyarakat Universitas Nusa Cendana Kupang - Klara Lestari, Hilgada; Yerlinda Carlista Mage, Mernon; Purnamasary Panis, Marleny (Green Publisher Indonesia, 2024)
Career Development is a career planning process provided by a company to individuals as an effort or opportunity to enhance and develop their careers to a higher level according to their abilities and responsibilities. This study aims to determine the effect of work motivation on the career development of lecturers in the Faculty of Public Health at Nusa Cendana University, Kupang. The research is quantitative in nature. The population consists of 71 lecturers, with a sample of 41 respondents selected using purposive sampling technique. Data collection was conducted using a work motivation scale and a career development scale with a Likert scale model. The collected data were analyzed using the Statistical Package for Social Sciences (SPSS) 16.0 for Windows program. Data analysis was carried out using a simple linear regression test. The results showed that the calculated F-value was 54.237 with a significance value of 0.000 < 0.05, which indicates that work motivation has an effect on career development. It is recommended to take advantage of the career development opportunities that have been organized and facilitated to achieve the desired career level. Based on the quantitative research conducted on the lecturers of the Faculty of Public Health at Nusa Cendana University, Kupang, it was found that work motivation influences career development